Views of parameter space: topographer and resident - Rees Mary (Paris Societe Mathematique De France, 2003)
This volume obtains a complete topological description of the spaces under consideration, from two points of view, i.e, the Topographer's View and the Resident's View. The Topographer's View is, in essence, a geometrising theorem. It shows that the space
Keywords: Branched coverings; Critical point; Rational maps; Teichmuller space